Genome-Wide Scan for Visceral Leishmaniasis in Mixed-Breed Dogs Identifies Candidate Genes Involved in T Helper Cells and Macrophage Signaling. - Yuri T Utsunomiya; Érica S Ribeiro; Amanda P N Quintal; Juliano R Sangalli; Valquiria R Gazola; Henrique B Paula; Cristiana M Trinconi; Valéria M F Lima; Silvia H V Perri; Jeremy F Taylor; Robert D Schnabel; Tad S Sonstegard; et al. (PLoS ONE, 2015)
We conducted a genome-wide scan for visceral leishmaniasis in mixed-breed dogs from a highly endemic area in Brazil using 149,648 single nucleotide polymorphism (SNP) markers genotyped in 20 cases and 28 controls. Using a mixed model approach, we found two candidate loci on canine autosomes 1 and 2. The positional association on chromosome 2 mapped to a predicted DNAse sensitive site in CD14+ monocytes that serve as a cis-regulatory element for the expression of interleukin alpha receptors 2 (IL2RA) and 15 (IL15RA). Both interleukins were previously found to lead to protective T helper 1 cell (Th1) response against Leishmania spp. in humans and mice. The associated marker on chromosome 1 was located between two predicted transcription factor binding sites regulating the expression of the transducin-like enhancer of split 1 gene (TLE1), an important player in Notch signaling. This pathway is critical for macrophage activity and CD4+ T cell differentiation into Th1 and T helper 2. Together, these findings suggest that the human and mouse model for protective response against Leishmania spp., which involves Th1 and macrophage modulation by interleukins 2, 15, gamma interferon and Notch signaling, may also hold for the canine model.